Ion‐Scale Magnetic Flux Rope Generated From Electron‐Scale Magnetopause Current Sheet: Magnetospheric Multiscale Observations. Issue 3 (24th March 2023) - Hasegawa, H.; Denton, R. E.; Dokgo, K.; Hwang, K.‐J.; Nakamura, T. K. M.; Burch, J. L.
Abstract: We present in‐depth analysis of three southward‐moving meso‐scale (ion‐to magnetohydrodynamic‐scale) flux transfer events (FTEs) and subsequent crossing of a reconnecting magnetopause current sheet (MPCS), which were observed on 8 December 2015 by the Magnetospheric Multiscale spacecraft in the subsolar region under southward and duskward magnetosheath magnetic field conditions. We aim to understand the generation mechanism of ion‐scale magnetic flux ropes (ISFRs) and to reveal causal relationship among magnetic field structures, electromagnetic energy conversion, and kinetic processes in magnetic reconnection layers. Results from magnetic field reconstruction methods are consistent with a flux rope with a length of about one ion inertial length growing from an electron‐scale current sheet (ECS) in the MPCS, supporting the idea that ISFRs can be generated through secondary reconnection in an ECS. Grad‐Shafranov reconstruction applied to the three FTEs shows that the FTEs had axial orientations similar to that of the ISFR. This suggests that these FTEs also formed through the same secondary reconnection process, rather than multiple X‐line reconnection at spatially separated locations. Four‐spacecraft observations of electron pitch‐angle distributions and energy conversion rate j · E ′ = j · E + v e × B j· E^′ =j· (E+v_e× B) suggest that the ISFR had three‐dimensional magnetic topology and secondary reconnection was patchy or bursty. Previously reported positive and negative values of j · E ′ j· E^′ , with magnitudes much larger than expected for typical MP reconnection, were seen in both magnetosheath and magnetospheric separatrix regions of the ISFR. Many of them coexisted with bi‐directional electron beams and intense electric field fluctuations around the electron gyrofrequency, consistent with their origin in separatrix activities. Plain Language Summary: Magnetic reconnection is a physical process that converts magnetic energy into plasma energy by changing the connectivity of magnetic field lines from one region to another. Magnetic reconnection at the outer boundary of planetary magnetospheres, known as the magnetopause (MP), is key to the entry of solar wind plasma and energy into the magnetospheres that forms the basis for space weather phenomena in the magnetospheres. MP reconnection often occurs in a transient or patchy manner, forming magnetic flux ropes (FRs) with helical field lines of various sizes. They may become an important pathway for fast coupling between the solar wind and magnetosphere. However, the generation mechanism of a subclass of FRs, relatively small "ion‐scale" FRs, is poorly understood. Computer simulations show that they are formed in thin and elongated current sheets of single active reconnection site, but this scenario has not been confirmed by observations. Our observations based on NASA's Magnetospheric Multiscale mission show that ion‐scale FR can form in a thin current sheet of single ongoing reconnection site at Earth's MP. The observed FR showed signatures of complex field line connectivity and localized conversion from electromagnetic to electron energy and vice versa, indicating complex MP dynamics. Key Points: Ion‐scale magnetic flux rope (ISFR) can be generated from reconnecting electron‐scale current sheet at the subsolar magnetopause (MP) Preceding mesoscale flux ropes had axial directions akin to that of the ISFR in the MP, suggesting the same generation mechanism The ISFR had complex magnetic topology with three‐dimensional effects and involved patchy, intense energy conversion in separatrix regions